Planet earth: mountains - Iyer, Rani (New Delhi The Energy and Resource Institute, 2011)
About 30 per cent of our earth is covered by mountains, which are home to unique plants and animals. But what are mountains and how are they formed? What can we find in a mountain? How do mountains affect the climate? Explore the mountains of the world and learn about the plant and animal life, the vegetation, the people, and how climate change is posing a danger to mountainous regions.
Keywords: Planet; Mountains